Analisis Pengaruh Kualitas Layanan Dan Fasilitas Terhadap Niat Berkunjung Kembali Yang Dimediasi Oleh Kepuasan Pelanggan Pada Hotel Ramah Muslim Di Mataram - Pratama, Ivan; Permadi , Lalu Adi (Universitas Mataram, 2025)
This study aims to test and analyze the Influence of Service Quality and Facilities on Revisit Intentions at Muslim-Friendly Hotels in Mataram City. The sample in this study amounted to 100 samples. The sampling technique in this study used a nonprobability sampling technique with a purposive sampling method. The analysis tool used in this study was SmartPLS version 4. The results of statistical data testing and analysis showed that all statement items in the study were declared valid. The results showed that service quality had a positive and significant effect on revisit intentions. Facilities had a positive and significant effect on revisit intentions. Service quality had a positive and significant effect on customer satisfaction. Facilities had a positive and significant effect on customer satisfaction. Customer satisfaction had a positive and significant effect on revisit intentions. Customer satisfaction mediated the effect of service quality positively and significantly. Finally, the mediating effect of customer satisfaction on revisit intentions positively and significantly.